A critical focus on men and masculinities in a feminist pedagogy: Lessons from the GREAT training course - Mwiine, Amon Ashaba; Mangheni, Margaret Najjingo; Asiimwe, Elizabeth; Businge, Martha; Sanya, Losira Nasirumbi (Makerere University, 2023)
Masculinities (just like femininities) are socially produced in varying agricultural contexts and are closely interconnected with men and women farmers’ everyday lives; hence critical reflection on these interconnections should be part and parcel of gender training in agriculture research to ensure sustainable gender transformation. Building capacities in gender analysis that includes a focus on men and masculinities is core to transforming deep-rooted social norms and practices that limit attainment of gender equality, yet there is insufficient empirically tested pedagogical models for this purpose. In this paper, we focus on the Gender-responsive Researchers Equipped for Agricultural Transformation (GREAT) capacitybuilding model that introduced sessions on men and masculinities in its training curriculum in the context of feminist pedagogy principles. Using selected experiences from transformative gender training for non-gender-specialist biophysical and social science agricultural research practitioners from sub-Saharan Africa and Southeast Asia, we take stock of the GREAT model’s motivation to include masculinities, the pedagogical approach used, and participants’ reactions and feedback on the value of understanding masculinities in gender-responsive agricultural research and their experiences with the sessions. We use systematic evidence from internal and external monitoring evaluation and learning data to draw lessons learned through these pedagogical practices and the implications training on masculinities and agriculture has for transforming agricultural food systems.